Cardiovascular disease assessment in rheumatoid arthritis: a guide to translating knowledge of cardiovascular risk into clinical practice. Issue 7 (7th March 2014) - Semb, Anne Grete; Rollefstad, Silvia; van Riel, Piet; Kitas, George D; Matteson, Eric L; Gabriel, Sherine E
Abstract : As physicians we like to have evidence for making decisions about interventions to improve health. The evidence vacuum in the field of cardiovascular disease (CVD) prevention and clinical outcome in patients with rheumatoid arthritis (RA) has received vigorous attention in the recent literature. There is broad agreement that a patient with RA fulfilling the criteria established for the general population on CVD risk reduction should receive proven interventions, including smoking cessation, weight reduction, blood pressure control and lipid-lowering therapy. In accordance with these recommendations, and despite all the uncertainties about CVD treatment threshold, targets and outcome results in RA, we firmly advocate that CVD risk should be assessed and acted on in patients with RA as recommended for the general population, even while educational CVD-preventive programmes are being developed and hard CVD end point studies are undertaken in this patient population. The initial strategies for implementing CVD risk evaluation will necessarily be modest at first. There are several possible strategies for collection of data that can be incorporated into the daily routine during rheumatology consultations at outpatient clinics. We recommend starting with these simple procedures: 1. CVD risk factor recording and evaluation using risk calculators available for the general population 2. Referral of patients with high CVD risk to a primary care physician or a cardiologist skilled in this subject for follow-up 3. Providing information about excess CVD risk and how to modify it to the patients as major stakeholders